Fresh fruit consumption in relation to incident diabetes and diabetic vascular complications: findings from the China Kadoorie Biobank Study. (November 2016) - Du, Huaidong; Li, Liming; Bennett, Derrick; Guo, Yu; Turnbull, Iain; Yang, Ling; Bragg, Fiona; Bian, Zheng; Chen, Yiping; Chen, Junshi; Millwood, Iona; Sansome, Sam; et al.
Abstract: Background: Although fresh fruit consumption has well recognised health benefits, substantial uncertainties remain about its potential effects on incident diabetes and, among those with diabetes, the risks of death and vascular complications. We aimed to assess the associations of fresh fruit consumption with the risk of incident diabetes and diabetic vascular complications. Methods: The China Kadoorie Biobank Study is a prospective cohort study with 512 891 Chinese adults aged 30–79 (mean 51·5, SD 10·7) years recruited from ten diverse localities across China between June 25, 2004, and July 15, 2008. At baseline and during the two subsequent resurveys (conducted from June to October, 2008, and from August, 2013, to September, 2014), data on fresh fruit consumption were collected with interviewer-administered electronic questionnaires. Deaths and information on hospital admissions were collected through linkages with death and disease registries and national health insurance claim databases. For each disease endpoint (including incident diabetes and, among baseline diabetics, mortality and hospital admissions of diabetic vascular complications) associated with fresh fruit consumption, we used Cox regression analysis to derive adjusted hazards ratios (HRs), adjusting for age, sex, region, education, income, smoking, alcohol consumption, physical activity, survey season, family history of diabetes, BMI, and consumption of meat, dairy products, and preserved vegetables. Ethics approval was granted by ethics committees or institutional review boards at the University of Oxford, the Chinese Center for Disease Control and Prevention, the Chinese Academy of Medical Sciences, and all participating regions, and all participants provided written informed consent. Findings: During a mean of 7·2 years (SD 1·3) of follow-up, 9504 new diabetes cases were recorded in 482 591 participants without self-reported or screen-detected diabetes at baseline. In 30 300 (5·9%) participants who had diabetes at baseline, 3389 deaths, 9746 macrovascular events requiring hospital admission, and 1345 microvascular events were recorded. 96 586 (18·8%) of all participants reported daily consumption of fresh fruit (consumers) and 32 775 (6·4%) never or rarely consumed fresh fruit (non-consumers). The proportion of non-consumers was about three times higher in participants with baseline self-reported diabetes (17·9% [2893 of 16 162]) than in those with screen-detected diabetes (6·8% [958 of 14 138]) or no diabetes (6·0% [28 924 of 482 591]). In participants without diabetes at baseline, the adjusted HR for incident diabetes was 0·88 (95% CI 0·83–0·93) for daily consumers versus non-consumers, with a clear dose–response relation with the amount consumed. This association was consistent across subgroups of participants at different levels of diabetes risk. In participants with diabetes at baseline, increased fresh fruit consumption was associated with reduced risks of death and major vascular diseases, with adjusted HRs per daily portion being 0·83 (0·74–0·93) for all-cause mortality, 0·87 (0·82–0·93) for macrovascular complications, and 0·72 (0·61–0·87) for microvascular complications. The associations were similar in patients with self-reported diabetes and those with screen-detected diabetes, and were not modified by diabetes onset age, duration, or treatment. Interpretation: In Chinese adults, higher fresh fruit consumption was associated with a significantly lower risk of diabetes and, in those who already had diabetes, lower risks of death, and major vascular complications. Funding: Kadoorie Charitable Foundation (Hong Kong, China), UK Wellcome Trust, Chinese National Natural Science Foundation, British Heart Foundation, UK Medical Research Council, and Cancer Research UK.